Urban consolidation center or peer-to-peer platform? The solution to urban last-mile delivery - DENG, Qiyuan (Institutional Knowledge at Singapore Management University, 2021)
The growing population in cities and booming e-commerce activities create huge demand for urban last-mile delivery, exerting intense pressure on the cities' well-being. To keep congestion and pollution under control, a consolidator can operate an urban consolidation center (UCC) to bundle shipments from multiple carriers before the last-mile delivery. Alternatively, the consolidator can operate a peer-to-peer platform for the carriers to share delivery capacity. We provide guidance for the consolidator to choose between these two business models by comparative analysis. We capture the interactions between the consolidator and carriers using a game-theoretical framework. Under each business model, the consolidator first decides a price of delivery service to maximize her expected profit. Each carrier then observes his task volume, and decides whether to deliver on his own or use the consolidator's service to minimize his delivery cost. Under the UCC model, the carriers become more dependent on the UCC as their variable delivery cost increases. Under the platform model, the demand and the supply of delivery capacity on the platform are balanced in equilibrium. Between the two business models, the UCC is more profitable than the platform if and only if the carriers' variable delivery cost is sufficiently large. Moreover, the UCC becomes more dominant as there are more carriers. The UCC is also more efficient than the platform in mitigating the negative social-environmental impact of urban last-mile delivery if and only if there are sufficiently many carriers. Otherwise, the platform performs better.